Hubungan antara Kematangan Emosi dengan Perilaku Konsumtif pada Mahasiswa Fakultas Syariah dan Hukum UIN Raden Fatah Palembang - Marisa Indah Leoni; Inda Purwasih (Indonesian Journal of Behavioral Studies, 2021)
This study aims to determine whether there is a relationship between Emotional maturity and Consumptive Behavior in Sharia and Law Students at UIN Raden Fatah Palembang. By using quantitative research methods. The population in this study were 200 students using Isaac Michael's table with an error rate of 5% and the sample used in this study was 127 students. The sample technique used in this study is a random sampling technique with a Likert scale. The data analysis method used is the product moment. It can be concluded that there is a significant relationship between Emotional Maturity and Consumptive Behavior. This is evidenced by the value of the correlation coefficient which shows the number 0.730 with a sig value. 0.000 where p < 0.05, meaning that the higher the emotional maturity, the lower the consumptive behavior of students, and vice versa, the lower the emotional maturity, the higher the consumptive behavior of students.